From Clan to Politics: A Feminist Analysis of the Reproduction of Patriarchy and Masculine Dominance in North Sumatra - Dominique Jacqualine Tirza; Erly Marlinda; Ika Arinia Indriyany (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to analyze the reproduction of patriarchy and masculine dominance in local politics in North Sumatra through a feminist perspective, highlighting the role of the patrilineal clan system in shaping social and political power structures. In Batak society, lineage is traced through men, thus positioning men as the successors of the clan and the primary representatives in both customs and social life. This condition causes male authority not only to remain within the family sphere but also extends into the public sphere, including local political practices. This study uses a qualitative approach with a desk study method through a review of literature, scientific journals, and regulations related to gender, customs, and local politics. The results show that patriarchy is reproduced through the clan system, customary practices, and the concept of Dalihan Na Tolu, which strengthens men's legitimacy in leadership and kinship-based power networks. In political contests, masculinity is often used as symbolic capital to gain voter trust, resulting in low female representation despite the 30 percent affirmative action quota policy. These obstacles are not only structural but also cultural, as customary norms still position men as more worthy figures for leadership. Therefore, efforts to achieve gender equality require changes not only in formal policies but also in cultural values and social practices within society.